FUNCTIONAL DYSPEPSIA IN PATIENTS WITH DIABETES MELLITUS TYPE 2 DIABETES AND METABOLIC SYNDROME - Abdusattarov A.A.; Zhurayeva M. A.; Sobirzhonova N.A. (Scholar Express Journals, 2023)
To evaluate the clinical manifestations of dyspepsia, depending on the course of diabetes mellitus and metabolic syndrome signs, in patients with diabetes mellitus type 2 without concomitant gastrointestinal diseases, that can cause dyspepsia. 107 patients of 212 people were included in the main phase of the study according to the inclusion and exclusion criteria. Dyspepsia was diagnosed in 76 patients (71.0%). Of them, 44 patients had no concomitant organic diseases of the gastrointestinal tract, which could explain dyspepsia (study group). Dyspepsia in study group patients was dyskinetic. Existence of dyspepsia was associated with the duration of diabetes mellitus type 2, presence of diabetic retinopathy, neuropathy, and coronary heart disease. Symptom of fullness in the epigastrium was associated with the presence of diabetic retinopathy, neuropathy and coronary heart disease, as well as the level of glycated hemoglobin A1c and postprandial glucose. Symptom of discomfort was associated with the duration of diabetes mellitus type 2, the presence of diabetic neuropathy, retinopathy, coronary heart disease, the level of postprandial blood glucose, basal blood glucose and glycated hemoglobin A1c. Symptom of nausea was associated with the presence of diabetic retinopathy. There was no association of dyspepsia as well and association of single dyspepsia symptoms in patients with diabetes mellitus type 2 and such signs of the metabolic syndrome as body mass index and the level of total serum cholesterol.
Keywords: Metabolic syndrome; dyspepsia; diabetes mellitus type 2